Pemberdayaan Masyarakat melalui Pilot Project Biochar Kopi Desa Rindu Hati Provinsi Bengkulu - Putri, Elsa Lolita; Utami, Kartika; Sari, Dyah Puspita; Ifebri, Rihan; Oktoyoki, Hefri (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2024)
Dedication to improving the productivity and welfare of coffee farmers in Rindu Hati village by using biochar made from coffee husk waste. The aim is to coordinate and socialize coffee farmers in increasing production and soil quality in coffee plantations in Rindu Hati village. The method used in this non-profit activity is Participatory Rural Appraisal (PRA) to share information within coffee farmer groups. Social service activities occur in Rindu Hat Village, Central Government of Bengkulu, Bengkulu Province. The target group is the Simpang Bening Farmer Group. The service was carried out through observation and field school to bio-talk coffee husk waste for members of coffee farmer groups in Rindu Hati Village, Central Bengkulu Administrative Region. The objectives of the activities carried out are to increase the understanding of Simpang Bening farmer groups about the utilization of coffee bean shell waste and the use of coffee biochar to increase production and soil fertility in the coffee plantation of Rindu Hati village.